Varicella Zoster Virus Meningo-Encephalo-Myelitis in an Immunocompetent Patient - Tavazzi, Eleonora (2008)
OBJECTIVE: To describe clinical, MRI and cerebrospinal fluid (CSF) features of a varicella zoster virus (VZV) related meningo-encephalo-myelitis (MEM) without rash in an immunocompetent female. PATIENT: An 85 year old immunocompetent woman with mild hyperthermia and acute, severe MEM. INTERVENTION: Serum antibodies and CSF PCR were searched for several viruses. Brain and spinal cord MRI were performed. Immunological profile. TREATMENTS: i.v. acyclovir 30 mg/kg/day; i.v. 6-MP 125 mg/day. RESULTS: Marked CSF lymphomonocytic pleocytosis, blood-brain-barrier damage, and PCR detection of 3.05 X 10 6 copies of VZV DNA. MRI revealed lesions of the meninges, brain and spinal cord. No evidence of immunosuppression. CONCLUSION: We highlight the importance of considering the possibility of VZV related MEM, even in immunocompetent patients. We also provide a MRI description of VZV related multifocal myelitis, not previously available. As supported by other reports, we underline the necessity of a prompt therapeutic intervention in this life-threatening condition